Less Is Better. Avoiding Redundant Measurements in Studies on Wild Birds in Accordance to the Principles of the 3Rs - de Jong, Adriaan (Frontiers in Veterinary Science, 2019)
The Principles of the 3Rs apply to animal use in research regardless where the research is conducted. In wildlife research, particularly research on wild birds, 3R implementation lags behind research using laboratory, farm, or pet animals. Raised 3R awareness and more field-adapted techniques and protocols are expected to improve the situation. Unpredictable access to animals entices the wildlife researcher to make the most of each caught animal, leading to potential over-use, and violation of the 3Rs. In this study, I statistically screened an existing set of Bean Goose biometric data for the presence of redundant measurements. The results show that it was possible to distinguish between the fabalis and rossicus subspecies (the original aim of the measurements) with fewer measurements (2 vs. 17). Avoidance of the redundant measurements was estimated to reduce both handling time and welfare impact with c. 80%. A robust scheme, supported by an R-script, is presented for continuously weeding out redundant measurements. This scheme is potentially applicable for measurement protocols in any wildlife study, and thus, contributes to the implementation of the principals of the 3Rs in wildlife research in general.